How to attract users come to the library / Muhammad Faris Mohammad Damanhuri and Muhammad Firdaus Ismail - Mohammad Damanhuri, Muhammad Faris; Ismail, Muhammad Firdaus (Faculty of Information Management, 2015)
This article intended to show on how to attract users come to the libraries. Several points will be explained and tips are available on how to encourage patrons come to library. Elements of attraction are very utmost important for maintaining user's visit to library. The library should become a place for searching knowledge, leisure and recreation and also a place where community meets. Attraction of users towards library identified mainly because of user's need and fulfilment of materials, good library environment, architecture factor, programmes, services and facilities and etc. The importance of this article to inform librarians on what should he or she do to encourage users to visit the library.